2019
DOI: 10.1111/jomf.12578
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Relationship Quality: Is There an Intergenerational Link?

Abstract: Objective: This study examines intergenerational continuities in relationship instability, general relationship quality, and intimate partner violence (IPV) between mothers and adolescents.Background: A growing body of literature has observed similarities in relationship quality between parents and their adult offspring. Less attention has focused on whether intergenerational continuities are present in adolescent relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 67 publications
0
14
0
1
Order By: Relevance
“…For example, those who experience a parental divorce were found to progress into dating much earlier than those from intact families, in particular when the divorce occurred in early adolescence (Ivanova et al, ). Using the Fragile Families and Child Wellbeing data set, Goldberg, Tienda, Eilers, and McLanahan (; https://fragilefamilies.princeton.edu/) found that adolescents' relationship experiences tended to mirror what they observed. For example, exposure to mothers' relationship instability in childhood was associated with adolescents' greater relationship instability.…”
Section: Romantic Relationships and Sexual Activity In Adolescence Anmentioning
confidence: 99%
“…For example, those who experience a parental divorce were found to progress into dating much earlier than those from intact families, in particular when the divorce occurred in early adolescence (Ivanova et al, ). Using the Fragile Families and Child Wellbeing data set, Goldberg, Tienda, Eilers, and McLanahan (; https://fragilefamilies.princeton.edu/) found that adolescents' relationship experiences tended to mirror what they observed. For example, exposure to mothers' relationship instability in childhood was associated with adolescents' greater relationship instability.…”
Section: Romantic Relationships and Sexual Activity In Adolescence Anmentioning
confidence: 99%
“…In it, the adolescents apprehend dynamics from observing their mothers, leading to the intergenerational continuity of healthy or violent relationships. This theory postulates the repetition of behavior patterns that the adolescents observed in their parents’ relationships ( 26 ) . Looking at the families of these adolescents can contribute to the advancement of this knowledge and to the understanding of how gender differences are built in the family dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The second outcome was a three‐level relationship variable that categorized participants' self‐assessed relationship quality at the point of each interview. Although not validated, other papers have used similar self‐assessments to measure relationship quality 27 . Categories included: not in an intimate relationship, in a good or very good intimate relationship with anyone, or in a fair, poor, or very poor intimate relationship with anyone.…”
Section: Methodsmentioning
confidence: 99%